2013. Procalcitonin Current State Evaluation Within a Large Health System. (26th November 2018) - Pena, Kelsey; Cooper, Mandelin; Greer, Nickie; Elders, Ty; Septimus, Edward
Abstract: Background: Procalcitonin is a hormone precursor that has been identified as a marker for bacterial infections. Procalcitonin increases as the body mounts an inflammatory response against infection, then returns to its normal range once the response subsides. Studies have shown that reduced procalcitonin levels may support antibiotic discontinuation. The purpose of this study was to determine how procalcitonin is being utilized at facilities within a large health system. Methods: From August 1, 2016 through July 31, 2017 facilities with a minimum of 30 procalcitonin levels were assessed. Patients who received antibiotics, with and without procalcitonin levels, were evaluated. The primary outcome was the frequency of multiple procalcitonin levels drawn 24–72 hours apart. Secondary analysis included baseline procalcitonin timing, antibiotic discontinuation based on procalcitonin thresholds (<0.5 or 80% reduction from a peak level), and monitoring patterns related to outcomes such as hospital length of stay (LOS), intensive care unit LOS, antibiotic duration of therapy, and hospital-onset Clostridium difficile infections. Data were obtained from a centralized, enterprise data warehouse. The study was approved by the University of Tennessee Health Science Center Institutional Review Board. Results: A total of 1, 005, 377 patients on antibiotics from 136 facilities were included. Procalcitonin levels were evaluated for 103, 913 of these patients. Within the procalcitonin group, 96% had their first procalcitonin drawn within 36 hours of the first antibiotic dose and 70% of patients had a single procalcitonin level drawn. Of those with multiple levels, 23% had levels drawn 24–72 hours apart. Only 32% had antibiotic therapy discontinued within 36 hours of meeting threshold. Conclusion: There is wide variability among facilities regarding procalcitonin use and monitoring. Baseline procalcitonin levels were drawn appropriately for most patients. Opportunities exist to standardize monitoring and encourage discontinuation of antibiotics when thresholds are reached. The findings of this analysis will be used to aid efforts to establish a health-system wide procalcitonin monitoring protocol to support antibiotic and laboratory stewardship. Disclosures: All authors: No reported disclosures.